3D LOOP PRODUCTS AND METHODS FOR PREPARING SAME

JP2025505579APending Publication Date: 2025-02-28DOW GLOBAL TECHNOLOGIES LLC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024545942
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-02-09
Publication Date
2025-02-28

Smart Images

  • Figure 2025505579000004
    Figure 2025505579000004
  • Figure 2025505579000001
    Figure 2025505579000001
  • Figure 2025505579000002
    Figure 2025505579000002
Patent Text Reader

Abstract

A 3D loop product made from a material comprising polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, wherein the material has a calculated low perfection crystalline melting enthalpy of 30 J / g or less within the temperature range of 15 to 80°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to 3D loop products and methods for preparing the same.

[0002] Introduction Polyethylene (PE) or polyolefin elastomer (POE) has been successful in 3D loop (3DL) applications such as mattress and pillow applications. Compared with polyurethane (PU) foam, polyethylene (PE) or polyolefin elastomer (POE) 3D loop cushioning has excellent breathability, easy cleanability, and is also inherently recyclable. Based on these advantageous properties, 3D loop cushioning has great potential for automotive seating applications. However, a significant challenge of heat resistance performance remains.

[0003] However, current POE or PE 3D loop cushioning formulations have poor compression set (>45%) at 70°C with a test compression set of 50% (ASTM D3574, part D), which is far removed from current PU foam properties.

[0004] Therefore, there remains a need for a 3D loop product having a compression set at 70° C. of 25% or less, preferably 20% or less. Summary of the Invention

[0005] After sustained research, the inventors have developed a POE / PE based 3D loop product that has a reduced enthalpy of fusion of low perfect crystals (calculated within the temperature range of 15-80°C) but still retains good elasticity and can meet the requirements of high temperature compression set (70°C) for automobile seats (ASTM D3574, Part D), i.e. not more than 25%, preferably not more than 20%, more preferably not more than 15%, and even more preferably not more than 10%.

[0006] In a first aspect of the present disclosure, the present disclosure provides a 3D loop product made from a material comprising polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, wherein the material has a calculated low perfection crystalline melting enthalpy of 30 J / g or less within a temperature range of 15 to 80° C.

[0007] Preferably, the polyethylene is selected from linear low density polyethylene (LLDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), or a mixture thereof, and the ethylene / α-olefin is selected from an ethylene / α-olefin random copolymer, an ethylene / α-olefin multiblock interpolymer, or a mixture thereof.

[0008] In a second aspect of the present disclosure, the present disclosure provides a method of producing a 3D loop product, comprising: extruding a material comprising polyethylene, an ethylene / α-olefin copolymer, or a blend of polyethylene and an ethylene / α-olefin copolymer; and carrying out a heat treatment at 70 to 90°C for 0.5 hours to 5 days. The method provides a material after heat treatment that has a calculated low perfection crystalline fusion enthalpy of 30 J / g or less within the temperature range of 15-80°C.

[0009] Preferably, the polyethylene is selected from linear low density polyethylene (LLDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), or a mixture thereof, and the ethylene / α-olefin is selected from an ethylene / α-olefin random copolymer, an ethylene / α-olefin multi-block interpolymer, or a mixture thereof.

[0010] In a third aspect of the present disclosure, the present disclosure provides a 3D loop product made by the process of the present disclosure.

[0011] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as claimed. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 shows the first heat DSC curve and low perfection crystalline melting enthalpy area (shaded region) of the 3D loop sample of Example B-8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and all publications, patent applications, patents, and other references mentioned herein are incorporated by reference.

[0014] Numerical ranges disclosed herein include all values ​​between the lower limit and the upper limit, inclusive. Ranges including explicit values ​​(e.g., 1 or 2, or 3-5, or 6, or 7) include any subranges between any two explicit values ​​(e.g., 1-2, 2-6, 5-7, 3-7, 5-6, etc.). Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all testing methods are current as of the filing date of this disclosure.

[0015] As disclosed herein, the terms "composition," "formulation," or "mixture" refer to a physical blend of different components obtained by simply mixing the different components by physical means. The sum of the weight percentages of each component in a composition is 100% by weight, based on the total weight of the composition.

[0016] As disclosed herein, "and / or" means "and, or alternatively." All ranges are inclusive of the endpoints unless otherwise indicated.

[0017] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same type or different types. Thus, the generic term polymer includes the term homopolymer (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure), and the term interpolymer, as defined herein below. Trace amounts of impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very small amounts ("ppm" amounts) of one or more stabilizers.

[0018] The crystalline structure of polyolefins is an important factor affecting the mechanical properties and heat resistance of polyolefin materials. The enthalpy of fusion is the energy required to melt a substance and is a parameter widely used for crystalline and semi-crystalline materials. Differential Scanning Calorimeter (DSC) is a common thermodynamic tool to directly evaluate the absorption and release of thermal energy that occurs in a sample during a controlled increase or decrease in temperature. Calorimetry is often applied to monitor phase transitions such as melting and crystallization. The enthalpy of fusion is determined from the total integrated heat flow within the thermogram peak, which indicates the total thermal energy absorption by the sample after appropriate baseline corrections that affect the transition. It is determined by shape analysis of an experimental graph of heat flow versus temperature.

[0019] A "polymer" is a compound prepared by polymerizing monomers, whether they are the same or different types of monomers. The molecular length (or molecular weight) and molecular structure of the individual polymer chains are not exactly the same, but have a distribution in length, weight, and structure. The distribution of comonomers within a copolymer may not be completely random due to factors such as the heterogeneity of the polymerization process or the heterogeneity of the catalytic comonomer incorporation. As a result, the crystalline structure of a semi-crystalline polymer is also a distribution of, for example, crystal size, crystalline uniformity, and crystalline melting temperature. As observed in a DSC calorimetry curve, the crystalline melting peak of a polymer is not as sharp as many single crystal structure materials, but covers a temperature range. For example, low density polyethylene may have a peak melting temperature of about 115°C, but still contains crystals that melt in a temperature range below 80°C. In this specification, the melting peak area of ​​15 to 80°C is used to define the melting temperature range of low perfection crystals.

[0020] Typically, crystallites of various sizes and melting points are formed when semi-crystalline polymers are cooled below the crystallization temperature. Smaller crystallites with lower melting temperatures and crystallites with some defects can be formed, referred to herein as "low perfection crystallites". Upon heating, the perfection of the crystallites improves and the melting temperature of these crystallites increases. The term "low perfection crystalline melting enthalpy" refers to the integrated area calculated within the temperature range of 15-80°C in the heating DSC curve of the 3D loop product described in this disclosure.

[0021] Materials for making 3D loop products The material may be at least 30% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 35% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 40% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 45% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 50% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 55% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 60% polyethylene, ethylene / α-olefin copolymer, or polyethylene, based on the total weight of the material. and ethylene / α-olefin copolymers, or at least 65% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 70% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 75% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 80% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 85% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 90% polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers, or at least 95% polyethylene, ethylene / α-olefin copolymers,or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 98% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or at least 99% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, or 100% polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer.

[0022] The polyethylene is selected from linear low density polyethylene (LLDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), or mixtures thereof. Suitable polyethylenes can be Elite™ 5815, Enhanced Polyethylene Resin, or EXCEED™ 3518CB, or blends thereof.

[0023] Preferably, the ethylene / α-olefin copolymer is selected from an ethylene / α-olefin random copolymer, an ethylene / α-olefin multi-block interpolymer, or a mixture thereof.

[0024] A) Ethylene / α-olefin random copolymer The ethylene / α-olefin copolymer is an ethylene / propylene random copolymer or an ethylene / C4-C8 α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer is an ethylene / C4-C8 α-olefin copolymer. The ethylene / C4-C8 α-olefin copolymer is composed or otherwise consists of ethylene in polymerized form and one copolymerizable C4-C8 α-olefin comonomer. The C4-C8 α-olefin comonomer may be selected from 1-butene, methyl-1-butene, 1-pentene, 1-hexene, 4-hexene, 5-methyl-1-hexene, 4-ethyl-1-hexene, or 1-octene.

[0025] The ethylene / α-olefin random copolymer may have a viscosity of from about 0.860 g / cc to about 0.965 g / cc, or from about 0.870 g / cc to about 0.925 g / cc, or from about 0.878 g / cc to about 0.920 g / cc, or from about 0.885 g / cc to about 0.918 g / cc, or from about 0.890 g / cc to about 0.915 g / cc, or from about 0.895 g / cc to about 0.912 g / cc, or from about 0.890 g / cc to about The ethylene / α-olefin random copolymers for the compositions of the present invention described herein having a density of 0.910 g / cc have a melt index (MI) at 190° C., 2.16 kg of about 40 g / 10 min or less, or about 30 g / 10 min or less, or about 25 g / 10 min or less, or about 22 g / 10 min or less, or about 20 g / 10 min or less, or about 18 g / 10 min or less, or about 15 g / 10 min or less. Alternatively, the ethylene / α-olefin random copolymers for the compositions of the invention described herein have a MI of from about 0.5 g / 10 min to about 40 g / 10 min, or from about 2.5 g / 10 min to about 38 g / 10 min or less, or from about 3 g / 10 min to about 30 g / 10 min or less, or from about 3 g / 10 min to about 25 g / 10 min or less, or from about 3 g / 10 min to about 20 g / 10 min or less, or from about 5 g / 10 min to about 18 g / 10 min or less, or from about 10 g / 10 min to about 15 g / 10 min or less.

[0026] A suitable ethylene / α-olefin random copolymer may be ENGAGE™ POE from Dow, such as ENGAGE™ 8401 POE, ENGAGE™ 8402 POE, ENGAGE™ 8450 POE, or ENGAGE™ 8480 POE, or blends thereof.

[0027] B) Ethylene / α-olefin multiblock interpolymer (OBC) As used herein, "ethylene / α-olefin multi-block interpolymer", also known as "olefin block copolymer (OBC)", refers to an interpolymer comprising ethylene and one or more copolymerizable α-olefin comonomers in polymerized form, characterized by a plurality of blocks or segments of two or more (preferably three or more) polymerized monomer units, which have different chemical or physical properties. Specifically, the term refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments (referred to as "blocks") linked in a linear fashion, i.e., chemically distinct units that are linked (covalently bonded) end-to-end with respect to polymerized functional groups, rather than in a pendant or grafted fashion. The blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene vs. polypropylene), size of crystallites resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching including long chain branching or hyperbranching, uniformity, and / or any other chemical or physical property. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distributions, based, for example, on the effectiveness of the use of a shuttling agent in combination with the catalyst system. Non-limiting examples of the olefin block copolymers of the present disclosure and processes for preparing same are disclosed in U.S. Pat. Nos. 7,858,706 (B2), 8,198,374 (B2), 8,318,864 (B2), 8,609,779 (B2), 8,710,143 (B2), 8,785,551 (B2), and 9,243,090 (B2), all of which are incorporated herein by reference in their entireties.

[0028] Ethylene / α-olefin multi-block interpolymers are characterized by multiple blocks or segments of two or more polymerized monomer units having differing chemical or physical properties.

[0029] In some embodiments, the multi-block copolymer may be represented by the following formula: (AB)n, where n is at least 1, and preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. "A" represents a hard block or segment, and "B" represents a soft block or segment. Preferably, the A and B segments are linked in a substantially linear fashion, as opposed to a substantially branched or substantially star-shaped fashion. In other embodiments, the A and B segments are randomly distributed along the polymer chain. In other words, for example, the block copolymer does not usually have the following structure: AAA-AA-BBB-BB. In still other embodiments, the block copolymer does not usually have a third type of block or segment that contains a different comonomer. In still other embodiments, each of the blocks A and B has a monomer or comonomer that is substantially randomly distributed within the block. In other words, neither block A nor block B includes two or more sub-segments (or sub-blocks) of distinct composition, such as a tip segment having a substantially different composition than the remainder of the block.

[0030] Olefin block copolymers are generally produced via a chain shuttling process, such as that described in U.S. Pat. No. 7,858,706, which is incorporated herein by reference. Some chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Some catalysts are listed in column 19, line 45 to column 46, line 19, and some cocatalysts are listed in column 46, line 20 to column 51, line 28. Some process features are listed in column 51, line 29 to column 54, line 56. See also: U.S. Pat. Nos. 7,608,668, 7,893,166, and 7,947,793, and U.S. Patent Publication No. 2010 / 0197880. See also U.S. Pat. No. 9,243,173.

[0031] Preferably, ethylene constitutes the majority mole fraction of the total ethylene / α-olefin multi-block copolymer, i.e., ethylene constitutes at least 50 mol% of the total ethylene / α-olefin multi-block copolymer. More preferably, ethylene constitutes at least 60 mol%, at least 70 mol%, or at least 80 mol%, with the substantial remainder of the total ethylene / α-olefin multi-block interpolymer comprising a C4-C8 α-olefin comonomer, preferably the C4-C8 α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene. In one embodiment, the ethylene / α-olefin multi-block interpolymer contains 50 mol%, or 60 mol%, or 65 mol% to 80 mol%, or 85 mol%, or 90 mol% ethylene. For many ethylene / octene multiblock interpolymers, the composition comprises an ethylene content of greater than 80 mol% of the total ethylene / octene multiblock interpolymer, and an octene content of 1 mol% to 20 mol%, or 10 mol% to 20 mol% of the total ethylene / octene multiblock interpolymer.

[0032] Ethylene / α-olefin multiblock copolymers contain various amounts of "hard" and "soft" segments. "Hard" segments are blocks of polymerized units in which ethylene is present in an amount of more than 90% by weight, or more than 95% by weight, or more than 95% by weight, or more than 98% by weight, up to 100% by weight, based on the weight of the polymer. In other words, the comonomer content (content of monomers other than ethylene) in the hard segments can be less than 10% by weight, or less than 5% by weight, or less than 5% by weight, or less than 2% by weight, based on the weight of the polymer, and as low as zero. In some embodiments, the hard segments contain all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units in which the comonomer content (content of monomers other than ethylene) is more than 5% by weight, or more than 8% by weight, or more than 10% by weight, or more than 15% by weight, based on the weight of the polymer. In one embodiment, the comonomer content of the soft segments can be greater than 20% by weight, or greater than 25% by weight, or greater than 30% by weight, or greater than 35% by weight, or greater than 40% by weight, or greater than 45% by weight, or greater than 50% by weight, or greater than 60% by weight, up to 100% by weight.

[0033] The soft segment may be present in the ethylene / α-olefin multiblock interpolymer at 1% by weight, or 5% by weight, or 10% by weight, or 15% by weight, or 20% by weight, or 25% by weight, or 30% by weight, or 35% by weight, or 40% by weight, or 45% by weight, or 50% by weight, or 55% by weight, or 60% by weight, or 65% by weight, or 70% by weight, or 75% by weight, or 80% by weight, or 85% by weight, or 90% by weight, or 95% by weight, or 99% by weight of the total weight of the ethylene / α-olefin multiblock interpolymer. Conversely, the hard segment may be present in a similar range. The weight percentage of the soft segment and the weight percentage of the hard segment may be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in U.S. Pat. No. 7,608,668, the disclosure of which is incorporated herein by reference in its entirety. Specifically, the weight percent of the hard and soft segments and the comonomer content can be determined as described in US Pat. No. 7,608,668, columns 57-63.

[0034] In one embodiment, the ethylene / α-olefin multi-block copolymers are produced in a continuous process and have a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When produced in a batch or semi-batch process, the ethylene / α-olefin multi-block copolymers have a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.

[0035] Non-limiting examples of suitable ethylene / α-olefin multi-block copolymers are disclosed in US Pat. No. 7,608,668, the entire contents of which are incorporated herein by reference.

[0036] In one embodiment, the ethylene / α-olefin multiblock copolymer is defined as having hard and soft segments, being styrene-free, consisting solely of (i) ethylene and (ii) a C4-C8 α-olefin, and having a Mw / Mn of 1.7-3.5.

[0037] The ethylene / α-olefin multi-block interpolymers have a density of about 0.860 g / cc to about 0.900 g / cc, or about 0.870 g / cc to about 0.895 g / cc, or about 0.880 g / cc to about 0.890 g / cc, and the ethylene / α-olefin multi-block interpolymers described herein have a MI of about 30 g / 10 min or less, or about 25 g / 10 min or less, or about 22 g / 10 min or less, or about 20 g / 10 min or less, or about 18 g / 10 min or less, or about 15 g / 10 min or less at 190 ° C., 2.16 kg. Alternatively, the ethylene / α-olefin multi-block interpolymers for the compositions of the invention described herein have a MI of from about 0.5 g / 10 min to about 30 g / 10 min, or from about 1 g / 10 min to about 25 g / 10 min, or from about 3 g / 10 min to about 20 g / 10 min, or from about 5 g / 10 min to about 18 g / 10 min, or from about 10 g / 10 min to about 15 g / 10 min.

[0038] A suitable ethylene / α-olefin multi-block interpolymer can be INFUSE™ from Dow, for example, INFUSE™ 9900OBC.

[0039] material The material for making the 3D loop product can include polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer. For example, the material for making the 3D loop product can include one or more ethylene / α-olefin random copolymers, one or more ethylene / α-olefin multiblock interpolymers, one or more polyethylenes, a blend of polyethylene and ethylene / α-olefin multiblock interpolymers, a blend of polyethylene and ethylene / α-olefin random copolymers, a blend of ethylene / α-olefin random copolymers and ethylene / α-olefin multiblock interpolymers, or a blend of polyethylene, ethylene / α-olefin random copolymers and ethylene / α-olefin multiblock interpolymers. The composition of the material for making the 3D loop product can vary, but has an overall MI and density.

[0040] Preferably, the material of the 3D loop product of the present disclosure has a density of about 0.880 g / cc to about 0.920 g / cc, preferably about 0.885 g / cc to about 0.918 g / cc, more preferably about 0.890 g / cc to about 0.915 g / cc, and even more preferably about 0.895 g / cc to about 0.912 g / cc.

[0041] Preferably, the material of the 3D loop product of the present disclosure has a MI of about 25 g / 10 min or less, preferably about 22 g / 10 min or less, more preferably about 20 g / 10 min or less, more preferably about 18 g / 10 min or less, at 190° C. and 2.16 kg. Alternatively, the material of the present disclosure has a MI of about 1 g / 10 min to about 25 g / 10 min, preferably about 3 g / 10 min to about 20 g / 10 min, more preferably about 5 g / 10 min to about 18 g / 10 min, and even more preferably about 8 g / 10 min to about 18 g / 10 min.

[0042] The material comprising polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer has a calculated low perfect crystalline fusion enthalpy of 30 J / g or less, or 29 J / g or less, or 25 J / g or less, or 22 J / g or less, or 21 J / g or less within the temperature range of 15 to 80°C.

[0043] Materials comprising polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers and having a low perfection crystalline melting enthalpy of 30 J / g or less, or 29 J / g or less, or 25 J / g or less, or 22 J / g or less, or 21 J / g or less calculated within a temperature range of 15 to 80° C. can be obtained through specially designed heat treatment or other methods, such as manufacturing process optimization, to provide an optimized crystalline structure. For example, the heat treatment temperature can be 70 to 90° C., preferably 80 to 90° C., for 0.5 hours to 5 days (or 4 hours to 30 hours, or 6 hours to 24 hours), preferably 80° C., for 1 hour to 2 days (or 4 hours to 30 hours, or 6 hours to 24 hours), or 90° C., for 4 hours to 5 days (or 4 hours to 2 days, or 6 hours to 24 hours).

[0044] Preferably, the materials for making the 3D loop product do not include styrene polymers.

[0045] In addition, the material may also contain added phthalate ester, trimellitate ester, fatty acid, epoxy, adipic acid ester, polyester, paraffin, naphthene, or aromatic plasticizers, known hindered phenol, sulfur, phosphorus, or amine antioxidants, hindered amine, triazole, benzophenone, benzoate, nickel, salicylic or other light stabilizers, antistatic agents, antibacterial agents, fluorescent brightening agents, fillers, flame retardants, flame retardant assistants, lubricants, and organic and inorganic pigments.

[0046] As the antioxidant, it is desirable to add at least one selected from known phenol-based antioxidants, phosphite-based antioxidants, thioether-based antioxidants, benzotriazole-based ultraviolet absorbers, triazine-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, NH-type hindered amine-based light stabilizers, and N-CH3-type hindered amine-based light stabilizers.

[0047] Examples of phenolic antioxidants include 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 4,4'-butylidenebis(6-tert-butyl-m-cresol), 3-(3,5-di-tert-butyl-4-hydroxyphenyl)stearylpropionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], Sumilizer AG80, and 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)mesitylene.

[0048] Examples of the phosphite antioxidant include 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 2,4,8,10-tetrakis(1,1-dimethylethyl)-6-[(2-ethylhexyl)oxy]-1,1-dimethylethyl- ... ]-12H-dibenzo[d,g][1,3,2]dioxaphosphocin, tris(2,4-di-tert-butylphenyl)phosphite, tris(4-nonylphenyl)phosphite, 4,4'-isopropylidenediphenol C12-15 alcohol phosphite, diphenyl(2-ethylhexyl)phosphite, diphenylisodecylphosphite, triisodecylphosphite, and triphenylphosphite.

[0049] Examples of thioether antioxidants include bis[3-(dodecylthio)propionate]2,2-bis[[3-(dodecylthio)-1-oxopropyloxy]methyl]-1,3-propanediyl, and 3,3'-ditridecylthiobispropionate.

[0050] The lubricant is selected from a hydrocarbon wax, a higher alcohol wax, an amide wax, an ester wax, a metal soap, and the like.

[0051] Preparation method The method of producing a 3D loop product of the present disclosure includes: extruding a material comprising polyethylene, an ethylene / α-olefin copolymer, or a blend of polyethylene and an ethylene / α-olefin copolymer; carrying out a heat treatment at 70 to 90°C, preferably 80 to 90°C, for 0.5 hours to 5 days (or 4 hours to 30 hours, or 6 hours to 24 hours), preferably at 80°C, for 1 hour to 2 days (or 4 hours to 30 hours, or 6 hours to 24 hours), or at 90°C, for 4 hours to 5 days (or 4 hours to 2 days, or 6 hours to 24 hours); The material after heat treatment has a calculated low perfect crystalline fusion enthalpy of 30 J / g or less within the temperature range of 15-80°C.

[0052] Extrusion Materials including polyethylene, ethylene / α-olefin copolymers, or blends of polyethylene and ethylene / α-olefin copolymers can be extruded to form 3D loop products.

[0053] Preferably, the extruded material has a density of from about 0.880 g / cc to about 0.920 g / cc, preferably from about 0.885 g / cc to about 0.918 g / cc, more preferably from about 0.890 g / cc to about 0.915 g / cc, and even more preferably from about 0.895 g / cc to about 0.912 g / cc.

[0054] Preferably, the extruded material has a MI of about 25 g / 10 min or less, preferably about 22 g / 10 min or less, more preferably about 20 g / 10 min or less, more preferably about 18 g / 10 min or less, at 190° C. and 2.16 kg. Alternatively, the extruded material has a MI of about 1 g / 10 min to about 25 g / 10 min, preferably about 3 g / 10 min to about 20 g / 10 min, more preferably about 5 g / 10 min to about 18 g / 10 min, and even more preferably about 8 g / 10 min to about 18 g / 10 min.

[0055] Preferably, the extruded material has a flexural modulus of at least 20 MPa, preferably at least 30 MPa, preferably at least 40 MPa, preferably at least 50 MPa, preferably at least 55 MPa, or even more preferably at least 60 MPa, but not more than 150 MPa, preferably not more than 140 MPa, preferably not more than 130 MPa, preferably not more than 120 MPa. The extruded material has a flexural modulus of 20 MPa to 120 MPa.

[0056] Heat Treatment After extrusion, heat treatment can be performed at 70 to 90°C, preferably 80 to 90°C, for 0.5 hours to 5 days (or 4 hours to 30 hours, or 6 hours to 24 hours), preferably at 80°C, for 1 hour to 2 days (or 4 hours to 30 hours, or 6 hours to 24 hours), or at 90°C, for 4 hours to 5 days (or 4 hours to 2 days, or 6 hours to 24 hours).

[0057] 3D Loop Products The set after compression set test was according to standard ASTM D3574 part D. The sample was compressed at 70°C for 22 hours with a compression set of 50%, then released and cooled at room temperature for 30 minutes, and then the set was measured. The 3D loop product of the present disclosure has a compression set at 70°C of 25% or less, or 24% or less, or 22% or less, or 20% or less, or 18% or less, or 15% or less, or 12% or less, or preferably 10% or less.

[0058] The 3D loop product of the present disclosure has a viscosity of 40 to 90 g / cm 3, or preferably 50 to 80 g / cm 3 , or more preferably 60 to 70 g / cm 3 , or even more preferably 65 to 70 g / cm 3 It has an apparent density of

[0059] The 3D loop product can be a cushion for a seat, a mattress, or a pillow. EXAMPLES

[0060] Certain embodiments of the present invention are now illustrated in the following examples in which all parts and percentages are by weight unless otherwise specified.

[0061] 1.Material Information on the raw materials used in the examples is listed in Table 1 below. [Table 1] *Unit: g / cm 3 **Unit: g / 10min, 190℃, 2.16kg

[0062] 2. Working Example [Example A-1 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8401 / EXCEED™ 3518CB 60 / 40 wt% / wt%. The density of the elastomer was 0.901 g / cm 3The melting point of the elastomer was 112°C. The MI of the elastomer was 10g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 62MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The 3D loop sample had good morphology for 3DL pad application.

[0063] [Example A-2 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The 3D loop sample had good morphology for 3DL pad application.

[0064] [Example A-3 of the present invention] A polyethylene-based thermoplastic elastomer was composited with ELITE™ 5815. The density of the elastomer was 0.910 g / cm 3The melting point of the elastomer was 123°C. The MI of the elastomer was 15g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 94MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 65 g / cm 3 The 3D loop sample had good morphology for 3DL pad application.

[0065] [Comparative example A-1] A polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8480. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 100°C. The MI of the elastomer was 1g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 83MPa. The samples were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to a molten state and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a sample. The sample had poor processability as indicated by the absence of curling of the fiber strands to form a 3D loop structure.

[0066] [Comparative example A-2] A polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402. The density of the elastomer was 0.902 g / cm 3 The melting point of the elastomer was 98°C. The MI of the elastomer was 30g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 72MPa. The samples were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the hole was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C), and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain the sample. This sample collapsed during production due to its too high MI.

[0067] [Comparative example A-3] A polyethylene-based thermoplastic elastomer was composited with HDPE HMA 016. The density of the elastomer was 0.956g / cm 3 The melting point of the elastomer was 133°C. The MI of the elastomer was 20g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 970MPa. The elastomer was too hard for seat cushioning applications.

[0068] [Comparative example A-4] A polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8200. The density of the elastomer was 0.870 g / cm 3 The melting point of the elastomer was 60° C. The MI of the elastomer was 5 g / 10 min (190° C., 2.16 kg). The flexural modulus of the elastomer was 10 MPa. The elastomer was too soft for seat cushioning applications. [Table 2] *Unit: g / cm 3 **Unit: g / 10min, 190℃, 2.16kg, ***MPa

[0069] In summary, for vehicle seating applications, the flexural modulus of the material composition should be in the range of 20-120 MPa to ensure a comfortable hardness range for the 3DL pad. Correspondingly, the density should be in the range of 0.880-0.920 g / cm 3 The MI range should be in the range of 3-20 g / 10 min (190 °C, 2.16 kg), because 3D loop pad structures made with high MI resins will collapse and 3D pad structures made with low MI resins will have difficulty achieving fiber curl during manufacturing.

[0070] [Example B-1 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company. The elastomer was fed into a single extruder to a molten state and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 1 hour, then removed from the oven and cooled to room temperature. The 70° C. compression set was 21% and the low perfection crystalline fusion enthalpy was 27.9 J / g.

[0071] [Example B-2 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 3 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 18%, and the low perfection crystalline fusion enthalpy was 27.1 J / g.

[0072] [Example B-3 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 6 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 15% and the low perfection crystalline fusion enthalpy was 25 J / g.

[0073] [Example B-4 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 22 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 13%, and the low perfection crystalline fusion enthalpy was 21.1 J / g.

[0074] [Example B-5 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 90° C. for 6 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 21% and the low perfection crystalline fusion enthalpy was 28.5 J / g.

[0075] [Example B-6 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 90° C. for 22 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 18%, and the low perfection crystalline fusion enthalpy was 28.9 J / g.

[0076] [Example B-7 of the present invention] A polyethylene-based thermoplastic elastomer was composited with ELITE™ 5815. The density of the elastomer was 0.910 g / cm 3The melting point of the elastomer was 123°C. The MI of the elastomer was 15g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 94MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 65 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 22 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 13.5% and the low perfection crystalline fusion enthalpy was 21.6 J / g.

[0077] [Example B-8 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 24 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 10%, and the low perfection crystalline fusion enthalpy was 21.1 J / g.

[0078] [Example B-9 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8401 / EXCEED™ 3518CB 60 / 40 wt% / wt%. The density of the elastomer was 0.901 g / cm 3The melting point of the elastomer was 112°C. The MI of the elastomer was 10g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 62MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 80° C. for 22 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 12%, and the low perfection crystalline fusion enthalpy was 20.1 J / g.

[0079] [Example B-10 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 80 g / cm. 3 The resulting 3D loop sample was heated in an oven at 80° C. for 24 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 11%, and the low perfection crystalline fusion enthalpy was 21.6 J / g.

[0080] [Example B-11 of the present invention] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 30 mm, and an apparent density of 50 g / cm. 3 The resulting 3D loop sample was heated in an oven at 80° C. for 22 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 15% and the low perfection crystalline fusion enthalpy was 24.5 J / g.

[0081] [Comparative example B-1] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 90° C. for 1 hour, then removed from the oven and cooled to room temperature. The 70° C. compression set was 28% and the low perfection crystalline fusion enthalpy was 33.3 J / g.

[0082] [Comparative example B-2] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The resulting 3D loop sample was heated in an oven at 90° C. for 3 hours, then removed from the oven and cooled to room temperature. The 70° C. compression set was 28% and the low perfection crystalline fusion enthalpy was 33.1 J / g.

[0083] [Comparative example B-3] A polyethylene-based thermoplastic elastomer was composited with ELITE™ 5815. The density of the elastomer was 0.910 g / cm 3The melting point of the elastomer was 123°C. The MI of the elastomer was 15g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 94MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 65 g / cm 3 The sample was not heat treated. The 70° C. compression set was 34% and the low perfection crystal fusion enthalpy was 32.5 J / g.

[0084] [Comparative example B-4] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 50 mm, and an apparent density of 70 g / cm 3 The sample was not heat treated. The 70°C compression set was 47% and the low perfection crystal fusion enthalpy was 32.7 J / g.

[0085] [Comparative example B-5] The polyethylene-based thermoplastic elastomer was composited with ENGAGE™ 8402 / ENGAGE™ 8450 60 / 40 wt% / wt%. The density of the elastomer was 0.902 g / cm 3The melting point of the elastomer was 97°C. The MI of the elastomer was 12g / 10min (190°C, 2.16kg). The flexural modulus of the elastomer was 65MPa. The 3D loop specimens were produced on a 3D loop production line (DIDA-1500) manufactured by DIDA machinery company as follows: the elastomer was fed into a single extruder to be in a molten state, and passed through a T-shaped die equipped with a circular hole array to produce a fiber melt. The diameter of the holes was 0.8mm, the distance between the holes was about 10mm, the length of the array was about 400mm, and the width of the array was about 50mm. The fiber melt was dropped into cooling water (about 30°C) and then pulled by a conveyor belt system at a controlled speed of about 0.5 meters / min to obtain a 3D loop specimen. The 3D loop specimens were then cut into the size (400mm x 400mm x 50mm) designed for testing. The obtained 3D loop sample had a fiber diameter of approximately 0.65 mm, a thickness of 30 mm, and an apparent density of 50 g / cm. 3 The sample was not heat treated. The 70° C. compression set was 50% and the low perfection crystal fusion enthalpy was 33.2 J / g. [Table 3] *Standard deviation is approximately 0.5 J / g.

[0086] 3. Testing Flexural modulus was measured on an Instron 5566 according to ASTM D790 at 1.36 mm / min.

[0087] Melt index (MI) was tested on a Tinius Olsen MP600 according to ASTM D1238 (test conditions: 2.16 kg, 190° C.).

[0088] The DSC was tested on a DSC-Q2000 according to the following method.

[0089] method 1: Equilibrate at 0°C 2: Data storage: On 3: 10°C / min gradient up to 200°C 4: Isothermal for 3 minutes 5: Mark the end of cycle 1 6: Gradient of -10°C / min to 0°C 7: Isothermal for 3 minutes 8: Marking the end of cycle 2 9: 10°C / min gradient up to 200°C 10: Mark the end of cycle 3 11: End of method

[0090] Compressive set: The compression set of the 3D loop specimens was measured according to ASTM D3574-2017. The specimens were 20 cm x 20 cm square 3D loop pads with a uniform thickness of approximately 5 cm. After compression at 50% strain for 22 hours at 70°C using a compression fixture, compression was removed and the 3D loop specimens were allowed to recover at room temperature for 30 minutes. The final specimen thickness was measured and the compression set was calculated using the following formula: Compression set (%) = ((T o -T f ) / T o ) x 100 In the formula, T o is the original sample thickness, T f is the final sample thickness.

[0091] Low-perfect crystal melting enthalpy calculation FIG. 1 is a schematic diagram of a 3D loop sample according to Example B-8 of the present invention. st Thermal melting DSC curves and low perfection crystal melting enthalpies are shown. The shaded area corresponds to the melting of low perfection crystals (temperature range: 15-80°C). The low perfection crystal melting enthalpy can be calculated by integrating the area between the melting curve and the baseline from 15-80°C as shown in the figure. Sixteen samples with different low perfection crystal melting enthalpies and the corresponding 3D loop specimen compressive residual strain properties at 70°C are reported in Table 3.

Claims

1. A 3D loop product made from a material comprising polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer, said material having a calculated low perfection crystalline melting enthalpy of 30 J / g or less within the temperature range of 15 to 80°C.

2. 2. The 3D loop product of claim 1, wherein the ethylene / α-olefin is selected from an ethylene / α-olefin random copolymer, an ethylene / α-olefin multi-block interpolymer, or a mixture thereof.

3. 10. The 3D loop product of claim 1, wherein the material has a calculated low perfection crystalline melting enthalpy of 29 J / g or less within a temperature range of 15-80°C.

4. 2. The 3D loop product of claim 1, wherein the material has a calculated low perfection crystalline melting enthalpy of 25 J / g or less within a temperature range of 15-80°C.

5. 10. The 3D loop product of claim 1, wherein the material has an MI of about 3 g / 10 min to about 20 g / 10 min.

6. The material has a viscosity of about 0.880 g / cm 3 ~Approx. 0.920g / cm 3 13. The 3D loop product of claim 1, having a density of

7. 10. The 3D loop product of claim 1, wherein the 3D loop product has a compression set of 25% or less at 70 degrees Celsius.

8. 10. The 3D loop product of claim 1, wherein the 3D loop product has a compression set of 20% or less at 70 degrees Celsius.

9. 10. The 3D loop product of claim 1, wherein the material has a calculated low perfection crystalline melting enthalpy of 21 J / g or less within a temperature range of 15-80°C.

10. 10. The 3D loop product of claim 1, wherein the 3D loop product is a cushioning material for a seat, a mattress, or a pillow.

11. extruding said material comprising polyethylene, ethylene / α-olefin copolymer, or a blend of polyethylene and ethylene / α-olefin copolymer; and carrying out a heat treatment at 70 to 90° C. for 0.5 hours to 5 days.

11. The method of manufacturing a 3D loop product according to any one of claims 1 to 10, wherein the material after heat treatment has a calculated low perfection crystalline melting enthalpy of 30 J / g or less within the temperature range of 15 to 80°C.

12. 12. A 3D loop product made by the process of claim 11.

Citation Information

Patent Citations

  • Method and article for producing a coiled filament nonwoven fabric web

    JP2015505912A

  • Three-dimensional crosspiece structure

    JP2016221250A

  • Buffer network structure and manufacturing method thereof

    JP2018507962A

  • Composite shock-absorbing structure and manufacturing method thereof

    JP2019523149A

  • Core material for cushion, and cushion

    WO2015125497A1